She did it! : 21 women who changed the way we think - McCully, Emily Arnold (Disney/Hyperion, 2018)
Highlights twenty-one women in history who left their mark on the nation and changed the way people think. Featured women range from Ida Minerva Tarbell and Madam C.J. Walker to Billie Jean King and Temple Grandin.